On Institutional Services from Foreign Students’ Perspective – What Makes a Higher Educational Institution Multicultural? - Böcskei, Elvira; Bács, Zoltán; Kovács, Barnabás; Tarnóczi, Tibor; Fenyves, Veronika (International Journal of Engineering and Management Sciences, 2018)
Higher education is of the utmost importance in terms of the competitiveness of every nation, including the Hungarian economy, therefore it is considered determinant for the future to survey student mobility of foreign students pursuing their studies in Hungary. Demographic decline that is characteristic to Hungary, already makes its influence felt in higher education, therefore internationalisation of institutions is of essential importance in terms of their operation and sustainability. Currently, it cannot remain unmentioned that it is a question of vital importance for domestic higher education institutions – and this process might only be further strengthened in the future – how they are able to compensate declining domestic demand by making their workshops attractive to foreign students and researchers.